2016
DOI: 10.1021/acs.nanolett.5b04761
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Ferrite Nanoparticles through Nonaqueous Redox Phase Tuning

Abstract: From magnetic resonance imaging to cancer hyperthermia and wireless control of cell signaling, ferrite nanoparticles produced by thermal decomposition methods are ubiquitous across biomedical applications. While well-established synthetic protocols allow for precise control over the size and shape of the magnetic nanoparticles, structural defects within seemingly single-crystalline materials contribute to variability in the reported magnetic properties. We found that stabilization of metastable wüstite in comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
100
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(106 citation statements)
references
References 44 publications
2
100
3
1
Order By: Relevance
“…39 Furthermore, a recent study showed that tuning the electrochemical potential of the solvent can influence the nature of the iron oxide phase obtained from synthesis. 49 …”
Section: The Magnetic Diameter – An Important But Often Neglected Promentioning
confidence: 99%
“…39 Furthermore, a recent study showed that tuning the electrochemical potential of the solvent can influence the nature of the iron oxide phase obtained from synthesis. 49 …”
Section: The Magnetic Diameter – An Important But Often Neglected Promentioning
confidence: 99%
“…Among advanced approaches for magnetic nanocrystal synthesis including co-precipitation reactions [8,9], sol-gel [10], hydrothermal/solvothermal [11], and microemulsion or microwave-assisted methods [12], the formation of monodisperse Fe 3 O 4 nanoparticles has been demonstrated with two typical wet chemical synthetic approaches: (I) solvothermal decomposition of iron (III) oleate complexes; and (2) reductively enhanced reaction using iron (III) acetylacetonate reagents with oleylamine under the reflux condition of high-temperature organic solvents [13][14][15]. While abundant chemical synthetic routes have been reported to obtain uniform magnetic nanostructures with size, shape and chemical composition control, however, the tailoring of enhanced pure phase over various iron oxide polymorphology remains a synthetic challenge without the constraint of size due to unstable nanoscale surface and interface which involved phase transformation resulting in unwanted core-shell nanostructures [13,16,17]. Here, we report a well-defined www.mdpi.com/journal/metals dimensional and phase-controlled synthetic method for magnetite nanostructures, assisted by alkaline metal precursors that show higher reduction potentials than that of iron complexes reagent.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report a well-defined www.mdpi.com/journal/metals dimensional and phase-controlled synthetic method for magnetite nanostructures, assisted by alkaline metal precursors that show higher reduction potentials than that of iron complexes reagent. Fe 3 O 4 nanoparticle is a common magnetic iron oxide nanostructure with an inverse spinel cubic structure in which oxygen forms a face-centered cubic (FCC) closed packing, and Fe cations occupy interstitial tetrahedral sites and octahedral sites [16]. In the case of organic phase synthesis, the high-temperature thermal decomposition of iron (III) oleate complexes in alkene hydrocarbon solvent (e.g., 1-octadecene) is a versatile method for monodisperse magnetite nanoparticles [13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations